Daya Anthelmintik Infusa Biji Buah Pinang (Areca catechu) Terhadap Cacing Ascaridia galli Secara in Vitro - Wida Wahidah Mubarokah; Wisnu Nurcahyo; Kurniasih Kurniasih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
A. galli infection caused high economic losses and decreased the amount and quality of egg production. The existence of anthelmintic resistance lead to the development of research on alternative treatments for A. galli. This aim of the research was to know LC50 of Areca catechu on infestation of A. galli. In this research A. galli was taken from a chicken slaughterhouse in Terban, Yogyakarta, and was divided into 8 groups for in vitro research. Group I was treated with an 10% infusion of A. catechu; group II was treated with 12.5% infusion of A. catechu; group III was treated with a 15% infusion of A. catechu; group IV was treated with a 17.5% infusion of A. catechu; group V was treated with 20% infusion of A. catechu; group VI was treated with a 22.5% infusion of A. catechu; group VII was treated with 25% A. catechu infusion and group VIII as negative control (0.9% NaCl). A. galli mortality is recorded every one hour until worm mortality is 100%. The results were then analyzed using the Reed and Muench method. Based on the in vitro test the infusion of Areca catechu against Ascaridia galli can cause death in worms with an LC 50 calculation of 21. 18%.